Pentingnya Membangun Budaya Literasi di Sekolah Dasar Islam Terpadu - Izzudin Hitimala (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to describe the implementation of literacy culture programs in elementary schools. This research uses a qualitative phenomenological approach. The subjects were school principals, teachers, students selected using purposive sampling techniques. Test the validity of the data using triangulation techniques by comparing the results of observations, interviews and documentation. The research results show that: 1) The policy of implementing a literacy culture in elementary schools using the government's School Literacy Movement program. This is based on Minister of Education and Culture Regulation no. 23 of 2015 which focuses on character development. (2) Implementation of literacy culture in elementary schools. This is based on the habituation stage which involves 10 minutes of reading the Koran and story books before learning. The activity development stage carried out was responding to the contents of reading books by reading independently, giving appreciation to students' literacy achievements, and having a school literacy team. The learning stage involves getting used to reading textbooks and using various strategies that support learning.